Fabrication of CVD graphene-based devices via laser ablation for wafer-scale characterization. (13th October 2015) - Mackenzie, David M A; Buron, Jonas D; Whelan, Patrick R; Jessen, Bjarke S; Silajdźić, Adnan; Pesquera, Amaia; Centeno, Alba; Zurutuza, Amaia; Bøggild, Peter; Petersen, Dirch H
Abstract: Selective laser ablation of a wafer-scale graphene film is shown to provide flexible, high speed (1 wafer/hour) device fabrication while avoiding the degradation of electrical properties associated with traditional lithographic methods. Picosecond laser pulses with single pulse peak fluences of 140 mJ cm −2 for 1064 nm, 40 mJ cm −2 for 532 nm, and 30 mJ cm −2 for 355 nm are sufficient to ablate the graphene film, while the ablation onset for Si/SiO2 (thicknesses 500 μ m/302 nm) did not occur until 240 mJ cm −2, 150 mJ cm −2, and 135 mJ cm −2, respectively, allowing all wavelengths to be used for graphene ablation without detectable substrate damage. Optical microscopy and Raman Spectroscopy were used to assess the ablation of graphene, while stylus profilometery indicated that the SiO2 substrate was undamaged. CVD graphene devices were electrically characterized and showed comparable field-effect mobility, doping level, on–off ratio, and conductance minimum before and after laser ablation fabrication.